Pengabdian Masyarakat Pelatihan Pembuatan Website PPDB dan Digital Marketing di SMA Bina Pendidikan 2 Bogor - Faik Bajsair; Karno Ganjar Prasetyo (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
The Indonesian Digital Business Polytechnic has made a significant contribution to SMA Bina Pendidikan 2 through the implementation of PPDB website training and digital marketing. This community service activity is a tangible form of the university's commitment to answering the challenges of the digital era. The issue and focus of this community service is that SMA Bina Pendidikan 2 has a shrinking number of students every year, this is due to the lack of massive new student registration information and the absence of technology to support PPDB SMA Bina Pendidikan 2. The implementation of PPDB Website Development & Digital Marketing Training at SMA Bina Pendidikan 2 Bogor, it is proven that teachers and staff have shown an increase in understanding related to the concept of website creation and digital marketing, which includes aspects of the target market, copywriting to procedures for creating a website. Teachers and staff learn that marketing schools is not only conventional strategies in this era, but also requires us to enter the world of technology and digital to reach a wider market, as well as increase publishers about schools. This increase in understanding is reflected in the results of the pre-test evaluation and material presentation which shows an increase in knowledge in understanding the concept of website creation and digital marketing.